Use of a simple pharmacokinetic model to study the impact of breast-feeding on infant and toddler body burdens of PCB 153, BDE 47, and DDE. (October 2017) - Lorber, Matthew; Toms, Leisa-Maree L.
Abstract: Several studies have examined the role of breast milk consumption in the buildup of environmental chemicals in infants, and have concluded that this pathway elevates infant body burdens above what would occur in a formula-only diet. Unique data from Australia provide an opportunity to study this finding using simple pharmacokinetic (PK) models. Pooled serum samples from infants in the general population provided data on PCB 153, BDE 47, and DDE at 6-month increments from birth until 4 years of age. General population breast-feeding scenarios for Australian conditions were crafted and input into a simple PK model which predicted infant serum concentrations over time. Comparison scenarios of background exposures to characterize formula-feeding were also crafted. It was found that the models were able to replicate the rise in measured infant body burdens for PCB 153 and DDE in the breast-feeding scenarios, while the background scenarios resulted in infant body burdens substantially below the measurements. The same was not true for BDE 47, however. Both the breast-feeding and background scenarios substantially underpredicted body burden measurements. Two possible explanations were offered: that exposure to higher BDE congeners would debrominate and form BDE 47 in the body, and/or, a second overlooked exposure pathway for PBDEs might be the cause of high infant and toddler body burdens. This pathway was inhalation due to the use of PBDEs as flame retardants in bedding materials. More research to better understand and quantify this pathway, or other unknown pathways, to describe infant and toddler exposures to PBDEs is needed. Highlights: Infant burdens of PCB 153, DDE, and BDE 47 were studied with a pharmacokinetic model. Breast-feeding was shown to result in elevated serum concentrations through age 4. The model predicted a rise in infant burdens from birth to 1 year not seen in data. Predictions of BDE 47 burdens fell short of observations; explanations were offered.